Experiences of Learners with Visual Impairments in Inclusive Schools in the Kingdom of Eswatini: A Scoping Review - Maguvhe Mbulaheni O; Maseko Nomsa Treasure (Acta Educationis Generalis)
Introduction: This article reports on experiences of teachers and learners with visual impairments (LVI) in inclusive high schools in the Kingdom of Eswatini.